Transaksi Nilai dalam Pembentukan Karakter Disiplin Santri di Pondok Pesantren Baitul Qur’an Wonogiri - Al Fani, Farid; Subando, Joko (TSAQOFAH, 2025)
The moral degradation observed among younger generations reflects a weakness in the internalization of values within formal education, highlighting the need for value-based educational institutions such as pesantren to comprehensively instill the character of discipline. This study aims to analyze the mechanisms of value transactions in shaping students’ (santri's) disciplinary character at Pondok Pesantren Baitul Qur’an Wonogiri. Value transaction is understood as the process of exchanging values through intensive social interactions among kyai, ustadz, and santri, both verbally and nonverbally, through role modeling, habituation, rules, reward and punishment systems, and collective activities. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Primary data sources include the pesantren leadership, mentoring ustadz, and students; secondary data were obtained from official pesantren documents. Data analysis follows the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The study seeks to identify the values being exchanged, describe the mechanisms of discipline formation through interactions within the pesantren, and uncover supporting and inhibiting factors in value internalization. Theoretically, the study contributes to the literature on community-based character education, while practically, it serves as a reference for pesantren in strengthening strategies for building student discipline.